Photochromic behavior of spiropyrans: the effect of substituent - Nadir, Najiah; Wahid, Zaharah; Zainuddin, Mat Tarmizi; Mohamed Islam, Noor Zalikha (Trans Tech Publications, Switzerland, 2014)
Spiropyrans are among the most promising organic p hotochromic dyes. However, spiropyrans are very sensitive dyes and there are m any independent factors that can affect the performance of these dyes. The effect of substituen t on the optical absorption spectra, fading kinetic, and also the dye stability of spiropyrans in diphenyl ether by UV irradiation has been investigated. The 6-nitro BIPS displayed greater ab sorbance intensity of 0.740% at 600nm compared to 8-ethoxy-6-nitro BIPS of 0.651% at 620n m. Furthermore, 6-nitro BIPS is less stable as it has higher rate constant of 0.1003s -1 and thus lower half-life time (50% decay of the photochromic effect) of 6.9s, in contrast to 8-etho xy-6-nitro BIPS of 0.0594s -1 and 11.7s respectively.